Perancangan Kontrak Berbasis Resiko Sosial Untuk Konflik Komunal dalam Transaksi Bisnis - Muhammad Is Haqqul Mubin; Hardian Iskandar (Riviera Publishing, 2025)
Business transactions involving local communities, especially in areas with a history of communal conflict or social vulnerability, often face more complex risks than conventional business risks. Conflicts triggered by social discontent, land issues, or unfair distribution of benefits can disrupt business operations and undermine social cohesion. This study aims to analyze the weaknesses of conventional business contracts that fail to anticipate social risks and formulate an effective model of designing social risk-based contracts to prevent communal conflicts between business people and communities, as well as mitigate the potential for communal conflicts, thereby promoting business sustainability and social welfare.